Epizoic diatoms on sea turtles and their relationship to host species, behaviour and biogeography: a morphological approach. Issue 4 (2nd October 2021) - Riaux-Gobin, Catherine; Ashworth, Matt P.; Kociolek, J.Patrick; Chevallier, Damien; Saenz-Agudelo, Pablo; Witkowski, Andrzej; Daniszewska-Kowalczyk, Genowefa; Gaspar, Cecile; Lagant, Magali; Touron, Margaux; Carpentier, Alice; Stabile, Vie; et al.
ABSTRACT: Sea turtles harbour epizoic diatoms of which several taxa are considered exclusively epizoic and possible 'commensals'. The epizoic diatom communities were examined from 124 individuals representing four turtle species ( Chelonia mydas, Eretmochelys imbricata, Lepidochelys olivacea and Dermochelys coriacea ), from three well-defined areas: Eastern Caribbean, Equatorial West Atlantic and South Pacific. Overall, the epizoic diatoms are very small and need electron microscopy to be accurately identified. Non-Metric MultiDimensional Scaling analyses permitted us to evaluate these diatom assemblages according to turtle species and biogeography. Differentiation was mainly driven by 14 taxa in the diatom genera Chelonicola, Tripterion, Tursiocola, Olifantiella, Navicula and Achnanthes . The highest diatom species richness was found associated with E. imbricata . Dermochelys coriacea and L. olivacea exhibit lower diatom diversities. Some difference in colonization was detected between C. mydas adults and juveniles at the same site, with higher diatom diversity for the juveniles. Within C. mydas we show geographic differentiation of their diatom assemblages, particularly between populations of the Equatorial West Atlantic and South Pacific. Two Tursiocola species 'commensal' to C. mydas seemed to be geographically restricted to French Guiana and the Caribbean. Dermochelys coriacea has a diatom assemblage very different from those of the three other turtles, probably due to its particular behaviour. Lepidochelys olivacea is also unique in the complete lack of Chelonicola species. Based on our results, the diatoms Tripterion societatis and Chelonicola spp. (as currently defined) appear to be mutually exclusive on turtle hosts. This study adds significantly to our understanding of the global distribution of epizoic diatoms on sea turtles. We discuss to what extent these diatoms can be used as a geographic marker with regard to the biogeography of the diatoms themselves and their host.